Implementation of Strategic Management in Improving Employee Performance at STIT Palapa Nusantara Lombok, NTB: Implementasi Manajemen Strategi dalam Meningkatkan Kinerja Pegawai STIT Palapa Nusantara Lombok NTB - Nasrullah (Institute of Educational, Research, and Community Service, 2023)
This study aims to investigate the implementation of strategic management in improving employee performance at Palapa Islamic College (STIT). This Islamic-based higher education institution plays a central role in shaping quality and competent human resources. The quality of graduates from STIT Palapa impacts the institution's image and reputation, as well as its contributions to society and religion. This research adopts a qualitative approach to gain a deeper understanding of the strategies adopted by STIT Palapa and their impact on employee performance. Data is collected through in-depth interviews with institutional leaders, management staff, and key employees, as well as through participatory observation and document analysis. The research findings indicate that STIT Palapa has formulated a comprehensive strategic plan focused on improving the quality of teaching, implementing technology, and developing employee professionalism. Through the active participation of all elements of the institution, STIT Palapa successfully integrates the strategies into daily practices and achieves its set objectives. The active involvement of employees in the formulation and implementation of strategies enhances their sense of ownership and commitment to the institutional goals, leading to higher work enthusiasm and motivation to achieve the set targets